3 - Traditional Igbo Numbering System: A Reconstruction: DOI: 10.4314/ad.v30i3.22228 - Ogomaka, Patrick Mathias C. (Africa Development, 2005)
This article presents the properties of the traditional and decimalized Igbo number systems and the principles governing their formulation. It looks at the cultural and religious uses of Igbo traditional number system and their implications for the development of curricular in not just mathematics and ethno-mathematics in tertiary level education, but also in arithmetic for primary and secondary school levels.